Construction of Highly Ordered ZnO–TiO2 Nanotube Arrays (ZnO/TNTs) Heterostructure for Photocatalytic Application - Xiao, Fang-Xing (ACS applied materials & interfaces, 2012)
In recent years, strenuous efforts have been devoted to exploring ZnO functionalized TiO2 nanotube arrays (ZnO/TNTs) nanocomposites; however, there is still a paucity of reports on the construction of well-defined ZnO/TNTs heterostructure via efficient and easily accessible approach. In this work, drawing on a two-step anodization combined pyrolysis strategy, we attained a highly ordered ZnO/TNTs hybrid nanostructure. Combined with a collection of characterizations including X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), diffusion reflectance spectrum (DRS), scanning electron microscopy (SEM), and transmission electron microscopy (TEM), we found that, in this coupling, in situ formed ZnO phases were uniformly grafted to TNTs framework giving rise to hybrid nanostructure, which is ascribed to cooperative interfacial interaction between polar TiO2 layer and ZnO precursor. The underlying interaction leading to judicious combination of TNTs and ZnO was unveiled by Fourier transformed infrared spectrum (FTIR) and XPS. Alternatively, it has been shown that ZnO nanocrystals distributed on the TNTs could serve as favorable hole channels and receptors for efficient separation of photoexcited charge carriers, which results in significantly enhanced photocatalytic performances of ZnO/TNTs heterostructure in comparison with pure TNTs, ZnO film, and P25 particulate film. Furthermore, it is found that the hybrid photocatalyst demonstrated excellent photostability. It is hoped that our work could present a straightforward paradigm for preparation of hierarchical semiconductor/1-D semiconductor heterostructures.